A Knight of the Nineteenth Century - Roe, Edward Payson, 1838-1888 (Salt Lake City, UT : Project Gutenberg, 2004)
"A Knight of the Nineteenth Century" by Edward Payson Roe is a novel written during the late 19th century. The story follows Egbert Haldane, a young man whose upbringing has fostered selfishness and tyranny, leading him down a path of moral ambiguity and reckless behavior. His journey explores themes of personal responsibility, the influences of upbringing, and the quest for redemption. The opening of the novel introduces us to Egbert Haldane and highlights the paradox of his upbringing: loved and idolized by his mother, yet nurtured in a manner that instills a sense of entitlement and disregard for others. Despite her intentions to provide him with a Christian education, Haldane grows to view his world with self-serving arrogance, leading him to engage in deceitful and irresponsible activities. As he approaches manhood, his misguided actions begin to surface, prompting concern from his mother and the community. The narrative sets the stage for Haldane's eventual confrontation with the consequences of his actions and positions the reader for themes of redemption and moral awakening as he encounters new influences in his life. (This is an automatically generated summary.)
Release date is 2004-08-01
Produced by Tom Allen, Juliet Sutherland, Charles Franks and the Online Distributed Proofreading Team
Keywords: Fiction